2018
DOI: 10.1038/s41396-018-0079-z
|View full text |Cite
|
Sign up to set email alerts
|

Depth matters: effects of precipitation regime on soil microbial activity upon rewetting of a plant-soil system

Abstract: Changes in frequency and amplitude of rain events, that is, precipitation patterns, result in different water conditions with soil depth, and likely affect plant growth and shape plant and soil microbial activity. Here, we used O stable isotope probing (SIP) to investigate bacterial and fungal communities that actively grew or not upon rewetting, at three different depths in soil mesocosms previously subjected to frequent or infrequent watering for 12 weeks (equal total water input). Phylogenetic marker genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(51 citation statements)
references
References 67 publications
3
45
3
Order By: Relevance
“…The soil bacterial community was more sensitive than the fungal community to flooding at the early stage as expected, which is consistent with the generally higher resistance to dry periods of fungi compared with bacteria [18,52]. Although we did not detect significant differences in bacterial 16s rRNA and fungal ITS abundance at the first 48 h after flooding, an earlier decline of bacterial 16s rRNA abundance indicated the sequential responses of bacterial community to water change ( Figure S2, bacteria at 48 h, fungi at 120 h after flooding in the potentially active community, respectively).…”
Section: Difference Between Bacterial and Fungal Community-level Respsupporting
confidence: 83%
See 1 more Smart Citation
“…The soil bacterial community was more sensitive than the fungal community to flooding at the early stage as expected, which is consistent with the generally higher resistance to dry periods of fungi compared with bacteria [18,52]. Although we did not detect significant differences in bacterial 16s rRNA and fungal ITS abundance at the first 48 h after flooding, an earlier decline of bacterial 16s rRNA abundance indicated the sequential responses of bacterial community to water change ( Figure S2, bacteria at 48 h, fungi at 120 h after flooding in the potentially active community, respectively).…”
Section: Difference Between Bacterial and Fungal Community-level Respsupporting
confidence: 83%
“…After flooding of dry soil, neither the total nor the potentially active fungal communities showed distinct changes over time at the phylum or class level, displaying a marked resistance to abrupt changes in water availability. Therefore, we did not expect most fungi to develop or be resuscitated successively in relative abundance after flooding since it is known that fungi are tolerant to moisture fluctuation resulting from their morphological life form with thick cell walls and well-developed hyphae, making them less dependent than bacteria on water film continuity to access nutrients [52,53]. However, we found a slightly changing trend of fungal community over time in our flooding experiment, given that oxygen concentration was revealed to decrease from 140 µM at the floodwater-soil interface to 0 µM detectably at a depth of approximately 2 mm and below with 7-days incubation [54,55].…”
Section: Difference Between Bacterial and Fungal Community-level Respmentioning
confidence: 99%
“…Furthermore, studies have shown that variation in both long-term and short-term SWC can alter the soil fungal community structure ( Pasternak et al, 2013 ; Evans et al, 2014 ; Hartmann et al, 2017 ; Engelhardt et al, 2018 ). Our study found that ST, SWC, NO 2 − -N, and soil pH were all important factors influencing soil fungal community variation ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…While mineralizable C has a statistically significant, positive relationship with relative yield in the fixed effect model, the mixed effects model showed that much of this was attributable to site-specific effects described by the www.nature.com/scientificreports www.nature.com/scientificreports/ random variable (Table 2). Aerobic respiration in surface soils is largely influenced by soil physiochemical characteristics, such as texture or bulk density [69][70][71] and climatic variables 72 . Here, we see the strong relationship between clay content and mineralizable C as a likely contributor to this site-specific effect (Tables S5 and S6).…”
Section: Lack Of Predictive Ability Of Mineralizable C Despite Beingmentioning
confidence: 99%